Taxonomy and ideology : on the boundaries of concept-classification - Fabian, Johannes (The Peter de ridder, 1975)
By choosing the title for this paper Iwish to indicate what I perceive to be polar positions in debates about the nature of cultural knowledge and, consequently, of expressions and possible descriptions of such knowledge..